New high‐resolution age data from the Ediacaran–Cambrian boundary indicate rapid, ecologically driven onset of the Cambrian explosion. (21st December 2018) - Linnemann, Ulf; Ovtcharova, Maria; Schaltegger, Urs; Gärtner, Andreas; Hautmann, Michael; Geyer, Gerd; Vickers‐Rich, Patricia; Rich, Tom; Plessen, Birgit; Hofmann, Mandy; Zieger, Johannes; Krause, Rita; et al.
Abstract: The replacement of the late Precambrian Ediacaran biota by morphologically disparate animals at the beginning of the Phanerozoic was a key event in the history of life on Earth, the mechanisms and the time‐scales of which are not entirely understood. A composite section in Namibia providing biostratigraphic and chemostratigraphic data bracketed by radiometric dating constrains the Ediacaran–Cambrian boundary to 538.6–538.8 Ma, more than 2 Ma younger than previously assumed. The U–Pb‐CA‐ID TIMS zircon ages demonstrate an ultrashort time frame for the LAD of the Ediacaran biota to the FAD of a complex, burrowing Phanerozoic biota represented by trace fossils to a 410 ka time window of 538.99 ± 0.21 Ma to 538.58 ± 0.19 Ma. The extremely short duration of the faunal transition from Ediacaran to Cambrian biota within less than 410 ka supports models of ecological cascades that followed the evolutionary breakthrough of increased mobility at the beginning of the Phanerozoic.